Metabolic molecular indicators of chronic stress in gilthead seabream (Sparus aurata) using comparative proteomics - Alves, Ricardo N. (2014)
The aim of this study was to identify possible metabolic molecular indicators of chronic stress in gilthead sea bream Sparus aurata. Two potential stressful conditions were tested: repeated handling and crowding at high stocking density. Gilthead seabream kept under optimized rearing conditions were used as control fish. Cortisol was measured as primary stress indicator and the liver proteome of stressed fish was compared to that of control fish using comparative proteomics. Plasma cortisol levels in sea bream repeatedly handled and crowded at high stocking density were significantly higher than in undisturbed control fish. A total of 560 spots were detected and the statistical analysis revealed a differential expression in about 50% of all detected proteins. Spots with greater than 2-fold or lower than 0.5-fold changes were identified by liquid chromatography–tandem mass spectrometry (LC–MS/MS). Proteins like fatty acid binding protein (lipid transport and antioxidant role), heat shock cognate protein (chaperoning), calmodulin (Ca2+ signaling), mitochondrial porine — voltage-dependent anion channel (lipid oxidation), glutamine synthetase (ammonia metabolism), cofilin and beta-tubulin (cytoskeleton), hemoglobin and several other proteins involved in carbohydrate metabolism (triose-phosphate isomerase, pyruvate dehydrogenase, glyceraldehyde 3-phosphate dehydrogenase, alfa-enolase) were differentially expressed in fish under chronic stress. Some of these proteins may be used in the future as chronic stress and/or part of a panel of welfare biomarkers, after validation studies using RT-PCR and ELISA assays.